Evaluate the performance of the agricultural initiative in the application of the Agricultural Cooperative Bank. - الجزراوي ابراهيم; العزاوي ابراهيم طارق (Journal of Economics and Administrative Sciences, 2013)
This paper deals with the process of evaluating the performance of agricultural activity in Iraq and in particular the agricultural initiative launched by Prime Minister Nuri al-Maliki, during the period from 2008 - 2011. Where it is possible to use criteria or indicators that are fabricated by a statement on the calendar and the results of which may be by comparing planned performance with actual performance or the evaluation of the actual performance of successive periods selected. With an emphasis on the agricultural initiative is subject to the evaluation process by implementing and destinations specialized loan funds its own projects as one of the agricultural lending. With the need to continue the implementation of the agricultural initiative because of its importance in supporting and developing Iraq’s agricultural sector which is in dire need of such initiatives at this time, as he has been emphasizing the need to increase the financial allocation for the Bank of Agricultural Cooperative as the agency responsible for disbursement of loans, agricultural initiative to Iraqi farmers and then retrieve them. The concluded the researchers to a set of conclusions reinforced the recommendations of the proposed benefit inevitably Iraq’s agricultural sector collapsed. ………………………………………